Rejecting the Radical New Left: Transformations in Japanese Social Movements - David H. Slater; Patricia G. Steinhoff (SocietàMutamentoPolitica: Rivista Italiana di Sociologia)
After a disastrous period of New Left political violence in the late 1960s and early 1970s, followed by two decades of abeyance, Japan has experienced a renewed era of social movement activity since the 1990s. These new movements explicitly seek to avoid contamination by the earlier period, even when their participants know little about it except for fear perpetuated by media portrayals of senseless violence. We analyze ethnographic accounts of contemporary groups engaged in collective action, ranging from small informal groups in Japan’s invisible civil society; groups trying to mobilize laborers who fall outside Japan’s traditional enterprise unions; and groups reviving and revitalizing older movement networks to deal with new threats; to new right-wing challengers and their counter-movements; and those making innovative use of cultural resources. They all seek alternatives to earlier social movements that engaged in political violence, by creating very different organizational structures and relations to ideology, relying on social media for communication, and developing new forms of collective action. They foreground cultural and expressive repertoires, and seek to establish the movement as a place of personal and social belonging. As was true of the New Left social movements in the mid-20th century, these new groups are closely attuned to movement developments around the world, even as they craft their responses to specific historical conditions in Japan.